Iserahan Ku Guru: Actualization of Value Education in Gayo Ethnic Society - Evanirosa Evanirosa; Ramsah Ali (Budapest International Research and Critics University, 2022)
This paper aims to reveal and analyze the meaning of tradition and value education contained in the culture of Iserahan ku Guru for children who start Islamic education in the Gayo Ethnic Society. This ethnic community is an indigenous tribe that is now threatened with extinction in the midst of the Aceh province which is dominated by the Acehnese. To respond to this, one of the solutions offered is the excavation and preservation of local wisdom values by re-actualizing the value education in the Gayo Ethnic community which has now faded and is almost lost, one of the values that must be maintained by the community is the Qur'anic value which used as the basis of life and the basis of Islamic education. The research method uses a qualitative approach, by exploring traditional leaders, community leaders from the Gayo tribe, and members of the community. This data collection uses observation, dialectics, in-depth interviews, and documentation. The results of the study show that the Gayo people are aware of the qur'ani values in the Iserahan ku Guru tradition which are starting to fade, so that awareness arises to actualize them again by thinking that in formal education, Iserahan ku Guru is made the norm of society in the culture of starting children's education and learning to teachers, The Iserahan Kuguru procession is a sacred ijab qabul as a pledge that binds both parties with a shared obligation to guide children towards Insan Kamil, historically the Iserahan Ku guru in its implementation started from non-formal education then progressed to formal education as a government program to preserve local Gayo culture as an actualization the obligation to seek knowledge that is commanded by religion.